A conceptual biomass liquefaction system with supercritical water for bio-oil, power and heating trigeneration: Thermodynamic and environmental analysis. (15th September 2021) - Yan, Shuo; Xia, Dehong; Mao, Rui; Liu, Xiangjun
Graphical abstract: Highlights: A novel biomass liquefication system with supercritical water (SCW) for bio-oil, power and heating is proposed. The highest energy and exergy efficiency reach 58.53% and 50.65% respectively. SCW reactor and heat exchanger contribute most to exergy and energy loss. From environmental assessment, a 0.36 kg CO2 equivalent is generated per kg of bio-oil produced with CCS. Thermodynamic and environmental performance are compared with other biomass-based energy conversion systems. Abstract: Advanced energy conversion systems on biomass-based are essential for high-efficient utilization of biomass energy. This work proposed a conceptual biomass liquefaction system with supercritical water for combined bio-oil, power and heating trigeneration. Both thermodynamic and life cycle environmental assessment are performed to verify the potential benefits of this novel system. Mass flow in the overall process is configured using Aspen Plus, with detailed energy and exergy flow modelling for the whole system. At the optimal operation parameters, where reactor temperature and pressure are around 390°C and 25 MPa, feedstock concentration is ∼33.3 wt%, water recycle ratio is ∼50%, and gas combustor temperature is about 1000°C, system energy and exergy efficiency reach their highest values, i.e. 58.53% and 50.65%, which are comparable to those of other biomass-based energy conversion system. Effects of those key parameters on exergy and energy efficiency are also discussed. The maximum exergy loss is induced by chemical exergy loss in liquefaction reactor and energy loss is mainly caused by heat transfer. From environmental assessment, GWP, AP, EP and TP values at the optimal operation parameters are lower than those of other biomass-based liquefaction system. When CCS and wastewater treatment units are applied, GWP, AP and EP values can be reduced by 50.0%, 33.2% and 61.5%, respectively. The comparison of thermodynamic and environmental performance among different biomass-based energy conversion systems shows that biomass liquefaction with SCW is a relatively efficient and clean technology to produce carbon-neutral bio-oil.